Shanxi province food security evaluation research - Jiayun Wang; Mingyu Tong (Scientific Reports)
Abstract Food security is the foundation of national security, which is related to economic development and social stability. Shanxi Province, as China’s grain production and marketing balance area, has rich agricultural resources and profound farming civilization, its food security situation is not only related to its own economic development, but also has a strategic position that can not be ignored in the national food security system. Based on the concept and goal of the development of food security in Shanxi Province, from the five aspects of quantity security, economic security, policy security, resource sustainability and ecological sustainability, this paper constructs the evaluation index system of food security in Shanxi Province, including the fluctuation rate of grain production and the sown area of grain, and establishes the entropy TOPSIS model to evaluate the development level of food security in Shanxi Province. The results show that the overall level of food security in Shanxi Province from 2001 to 2022 shows a trend of first decline and then rise, and the importance of food economic security, policy security and resource sustainability is increasing year by year. In the process of improving the level of food security development in Shanxi Province, it is also affected by structural imbalance, scientific and technological level, grain storage and transportation. Finally, the paper puts forward some policy suggestions to ensure food security in Shanxi Province.